Відповідність об’єднаних територіальних громад в Україні критеріям спроможності - Виногородська, Наталія Григорівна (Ірпінь, 2025)
Робота полягає в проведенні аналізу відповідності об’єднаних територіальних громад в Україні критеріям спроможності та розробки рекомендацій щодо підвищення їх ефективності. Проведено аналіз теоретичних та практичних засад формування об’єднаних громад в Україні; визначено основні критерії спроможності територіальних громад; встановлено фактори впливу на економічну стійкість громад; виявлено основні проблеми, що перешкоджають забезпеченню спроможності громад та запропоновано зміни до методики формування спроможних громад.

The work consists of conducting an analysis of the compliance of united territorial communities in Ukraine with the criteria of capacity and developing recommendations for improving their effectiveness. An analysis of the theoretical and practical principles of the formation of united communities in Ukraine was conducted; the main criteria for the capacity of territorial communities were determined; factors influencing the economic sustainability of communities were established; the main problems that hinder the capacity of communities were identified and changes to the methodology for the formation of capable communities were proposed.
Compliance of united territorial communities in Ukraine with capacity criteria
Keywords: органи місцевого самоврядування; об’єднана територіальна громада; реформа децентралізаці; спроможність громади; критерії спроможності; методика формування спроможних громад; local self-government bodies; united territorial community; decentralization reform; community capacity; capacity criteria; methodology for forming capable communities